9% Nickel Steels And Their Welding Behavior - Qumrul, Ahsan; Asma, Haseeb; Hussein, Nur Izan Syahriah; Chang, Siang Yee (Elsevier, 2014)
The 9% nickel steels were first developed by the International Nickel Company, USA, in 1942. The addition of 9% nickel to the steel followed by appropriate heat treatment yields a combination of high strength and excellent fracture toughness at cryogenic temperatures. Consequently, these steels have become the main materials of construction of welded tanks and vessels for the storage and transportation of liquefied natural gas (LNG). Welding, the main fabrication process for the construction of tanks and vessels, assumes an especially important role in the use of 9%Ni steels. Recent increase in the demand of LNG as a clean source of energy makes the 9% nickel steels even more important in the construction of welded cryogenic tanks and vessels. Demands for improved mechanical properties, better reliability, optimum usage of steel and lower cost are the main driving forces for new developments in this area. This chapter is intended to review the main aspects of the 9%Ni steels and their welding behavior in the current as well as future context.